ӘДЕТТЕГИ ДИФФЕРЕНЦИАЛЛЫҚ ТЕӉЛЕМЕЛЕР УШЫН ҚОЙЫЛҒАН КОШИ МӘСЕЛЕСИН САНЛЫ ШЕШИЎ УСЫЛЛАРЫНЫӉ ЭФФЕКТИВЛИЛИГИ БОЙЫНША САЛЫСТЫРМАЛЫ АНАЛИЗИ - Бектурсынова, Д.П. (FAN va JAMIYAT, 2020)
This article discusses one-step numerical methods for solving the Cauchy task for ordinary differential equations. A comparative analysis of the effectiveness of these numerical methods is implemented by using the example of solving the Cauchy task for an ordinary differential equation of the first order.